Pendampingan Demplot Teknik Budidaya Bawang Merah pada Musim Hujan Secara Ramah Lingkungan - Manan, Abdul; Soesanto, Loekas; Mugiastuti, Endang; Rahayuniati, Ruth Feti (Jurnal SOLMA, 2024)
Background: Shallot cultivation in the rainy season faces the constraints of more severe plant disease problems. Utilization of mixed biopestisda Trichoderma harzianum, Bacillus sp. B8 and Pseudomonas flourescens P8 as well as proper cultivation techniques have not been adopted by farmers. It is necessary to assist farmers in implementing the technology The objectives of the activity are: assisting farmers in implementing the shallot cultivation technology package appropriately, increasing the quantity and quality of crop production, and increasing farmers' income through increasing farm efficiency. Method: The farmers participating in the activity are members of the farmer group "Lestari" Tambak Sogra Village, Sumbang District, Banyumas Regency. Technology transfer method through demplot assistance. The biopesticide technology package and environmental manipulation are compared to the conventional package of synthetic chemical pesticides. Data on the growth and yield of technological plot crops compared to conventional plots. The large number of farmers who can independently apply the technology is observed.  Results: mentoring activities showed that farmer group members were able to independently implement technology packages. The use of biopesticides and proper cultivation techniques can produce growth and yield equivalent to the use of synthetic chemical pesticides. Conclusion: 80% partner farmers can apply technology packages, the use of biopesticides is able to substitute the use of synthetic chemical pesticides, technology packages are able to increase 5.9% of shallot bulbs and reduce 75% production costs.